COVID‐19 and Venous Thromboembolism in Intensive Care or Medical Ward. Issue 6 (23rd October 2020) - Avruscio, Giampiero; Camporese, Giuseppe; Campello, Elena; Bernardi, Enrico; Persona, Paolo; Passarella, Christian; Noventa, Franco; Cola, Marco; Navalesi, Paolo; Cattelan, Annamaria; Tiberio, Ivo; Boscolo, Annalisa; et al.
Abstract : Despite thromboprophylaxis, patients with coronavirus disease 2019 (COVID‐19) exhibit hypercoagulability and higher venous thromboembolic risk, although its real incidence is still unknown. The aim of this study was to evaluate the incidence of venous thromboembolism (VTE) in patients with COVID‐19 admitted to both intensive care units (ICUs) and medical wards (MWs). Consecutive patients admitted for COVID‐19 to the MW and the ICU at Padua University Hospital, all receiving thromboprophylaxis, underwent systematic ultrasonography of the internal jugular, and the upper and lower limbs veins every 7 days (± 1 day) after the admission; and, if negative, once‐weekly until discharge or death. In case of suspected pulmonary embolism, a multidetector computed tomographic angiography was performed. The primary outcome was the proportion of any deep‐vein thrombosis (DVT) and symptomatic pulmonary embolism in both groups. An extended blood coagulative test was performed as well. From March 4 to April 30, 2020, a total of 85 patients were investigated, 44 (52%) in MWs and 41 (48%) in the ICU. Despite thromboprophylaxis, VTE occurred in 12 patients in the MWs (27.3%) and 31 patients in the ICU (75.6%) with an odds ratio of 9.3 (95% confidence interval (CI) 3.5–24.5; P < 0.001). Multiple‐site DVT occurred in 55.6% of patients (95% CI 39.6–70.5). Increased D‐dimer levels significantly correlated with VTE ( P = 0.001) and death ( P = 0.015). Summarizing, patients with COVID‐19 admitted to the MW or ICU showed a high frequency of venous thromboembolism, despite standard‐dose or high‐dose thromboprophylaxis. Whether thrombosis, particularly asymptomatic events, may play a role in the morbidity and mortality of patients with COVID‐19 remain to be clarified.